Towards Gender Equity in Sports: Insights into the Under-Representation of Women in Sports Leadership in Kenya - Mwisukha, Andanje; Gitonga, Elijah; Mwangi Wanderi, Peter (ACTIVIDAD FÍSICA Y CIENCIAS / PHYSICAL ACTIVITY AND SCIENCE, 2022)
The question of under-representation of women in various fields of sport, including leadership is a historical phenomenon that has received attention in the contemporary world. Consequently, measures to address this imbalance are continuously being explored. This includes determining the root causes of the phenomenon and possible intervention measures. This study therefore, investigated the social, economic, political and cultural factors that influence women‟s participation in sports leadership in Kenya on the basis of the perceptions of key stakeholders in sports in the country (n=180). Findings revealed that there was interplay of social, economic, political and cultural factors in determining either the under-representation or enhancement of women‟s representation in sports leadership which need to be addressed by policy-makers.